2018
DOI: 10.5376/msb.2018.09.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Factors on Seed Germination of <i>Salix linearistipularis</i>

Abstract: This study evaluated the ecological risk assessment of heavy metals in cassava mill effluents contaminated soil in rural community in the Niger Delta region of Nigeria. Secondary data was used for the ecological risk assessment. Two background scenarios i.e. geometric mean (BGM) and median mean (BMM) was used as the reference value. The heavy metals that were assessed for ecological risk include viz: Cr, Zn, Cu, Co, Ni, Mn, Pb and Cd. 50% of mean detected individual heavy metals were considered for the locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Authors have variously reported that cassava mill affects microbial, heavy metal, and general physicochemical parameters of the receiving soil (Nwaugo et al, 2007(Nwaugo et al, , 2008Ehiagbonare et al, 2009;Eneje and Ifenkwe, 2012;Nwakaudu et al, 2012;Okechi et al, 2012;Osakwe, 2012;Chinyere et al, 2013;Izonfuo et al, 2013;Omotiama et al, 2013;Okunade and Adekalu, 2013;Ezeigbo et al, 2014;Ibe et al, 2014;Eze and Onyilide, 2015;Igbinosa, 2015;Igbinosa and Igiehon, 2015;Omomowo et al, 2015;Izah et al, 2017b).…”
mentioning
confidence: 99%
“…Authors have variously reported that cassava mill affects microbial, heavy metal, and general physicochemical parameters of the receiving soil (Nwaugo et al, 2007(Nwaugo et al, , 2008Ehiagbonare et al, 2009;Eneje and Ifenkwe, 2012;Nwakaudu et al, 2012;Okechi et al, 2012;Osakwe, 2012;Chinyere et al, 2013;Izonfuo et al, 2013;Omotiama et al, 2013;Okunade and Adekalu, 2013;Ezeigbo et al, 2014;Ibe et al, 2014;Eze and Onyilide, 2015;Igbinosa, 2015;Igbinosa and Igiehon, 2015;Omomowo et al, 2015;Izah et al, 2017b).…”
mentioning
confidence: 99%
“…35,[65][66][67][68][69] According to Izah et al, 67,68 the soil plays social, ecological and economic roles. This could be due to the fact that several activities are carried out in the soil.…”
Section: Role Of Biodiversity To the Ecosystem And Sustainable Develomentioning
confidence: 99%
“…In addition the soil environment is a major recipient of waste streams emanating from food processing including oil palm, 71 cassava processing. 35,[67][68][69]72 These wastes are rarely treated in Nigeria before disposal. After heavy precipitation they could be washed into the nearby surface water (major sink of pollutants) thereby causing an alteration in water and sediment quality depending on the constituents and concentration of toxicants/ hazardous substances found in the water.…”
Section: Soil Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous result from Izah et al (2017c) was used for the assessment of metal enrichment index (MEI), QoC, Igeo and EF of the heavy metals in cassava mill effluents contaminated soil (Table 1), while Improved Nemerow Index (INI) was computed based on the value obtained from the Igeo. The assessment was carried out under two background scenarios viz: geometric and median mean.…”
Section: Data Sourcementioning
confidence: 99%